Major provisions on trade in goods under the EPA\n - Humphrey, Errol (Barbados. Ministry of Foreign Affairs... Foreign Trade Division. EPA Implementation Unit BellevilleBB, 2011)
Provides concise information on the principal provisions of the Economic Partnership Agreement and how they might benefit Barbados.